Individual and concurrent effects of heat and drought stress on the growth and yield of two Malaysian rice cultivars - Sethuraman, Gomathy; Mohd Zain, Nurul Amalina; Osman, Normaniza; Ismail, Mohd Razi (Instituto De Investigaciones Agropecuarias, 2024)
Heat and drought stress, which often co-occur due to water evaporation, are two major abiotic factors limiting the production of rice (Oryza sativa L.) It is crucial to enhance understanding of the effects of these abiotic stresses in rice, particularly for rice-producing countries like Malaysia, which has yet to achieve rice self-sufficiency. This greenhouse study was conducted to evaluate the morphological changes of two important Malaysian cultivars (‘MR219’ and ‘MR303’) at vegetative, reproductive, and ripening stages, as well as their physiological response and yield components under normal (control), heat, drought, and combined heat-drought stress conditions. Individual heat stress greatly influenced rice growth and yield, with significant differences (p < 0.01) observed across all examined parameters except the grain to leaf area index ratio (GtoLAI). Conversely, individual drought stress mostly affected yield-related parameters, with significant differences (p < 0.01) in grain weight (GW), harvest index (HI), and percentage of filled grain (%FG). Interestingly, the combined stresses in this study did not significantly affect plant height (PH) for all growth stages and most yield-related traits (HI, GW, and GtoLAI). The majority of the significant changes (p < 0.01) were observed on physiological traits, including chlorophyll a (Chl A) and b (Chl B). We found a positive correlation between HI and %FG (R2 = 0.3974**) under heat and drought stress, indicating that improving either of these traits can boost rice production. Collectively, our study revealed that the individual effects of heat and drought on rice growth and yield can differ from the effects of combined stress.